2005
DOI: 10.1073/pnas.0408582102
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of Aβ protofibrils stabilized by a small molecule

Abstract: Metastable oligomeric and protofibrillar forms of amyloidogenic proteins have been implicated as on-pathway assembly intermediates in amyloid formation and as the major toxic species in a number of amyloid diseases including Alzheimer's disease. We describe here a chemical biology approach to structural analysis of A␤ protofibrils. Library screening yielded several molecules that stimulate A␤ aggregation. One of these compounds, calmidazolium chloride (CLC), rapidly and efficiently converts A␤(1-40) monomers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
134
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 31 publications
9
134
1
1
Order By: Relevance
“…However, it mostly remains unclear whether monomers, oligomers or protofibrillar structures are specifically targeted by modulators of amyloid aggregation 43,44 and whether compound effects on certain aggregate species (e.g. protofibrils) are toxic or beneficial for mammalian cells 13 . In this study, we have searched for small molecules that promote spontaneous A42 assembly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it mostly remains unclear whether monomers, oligomers or protofibrillar structures are specifically targeted by modulators of amyloid aggregation 43,44 and whether compound effects on certain aggregate species (e.g. protofibrils) are toxic or beneficial for mammalian cells 13 . In this study, we have searched for small molecules that promote spontaneous A42 assembly.…”
Section: Discussionmentioning
confidence: 99%
“…However, more detailed timeresolved studies with well-defined A42 aggregate species are necessary to compare the results obtained with O4 and methylene blue. While O4 promotes the formation of long amyloid fibrils the compound calmidazolium chloride (CLC) was shown to stabilize protofibrillar structures 13 . A stabilization of -sheet-rich, nontoxic, spherical A conformations was observed with the compound scyllo-inositol 47 , while the polyphenol EGCG was shown to convert A42 peptides into non-toxic, unstructured oligomers 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether some of these species represent off-or on-pathway intermediates to amyloid fibril formation remains unknown. Some of the key distinguishing features of protofibrillar aggregates are that they (i) contain a mixture of different secondary structure elements with a predominance of β-sheet 20 ; (ii) bind amyloid-specific dyes, such as Congo red and Thioflavin-T (ThT), although less strongly than mature fibrils [20][21][22] ; and (iii) are less stable than mature amyloid fibrils and exist in equilibrium with monomeric Aβ 20,21,23 . In the presence of monomeric Aβ, all these species convert to mature amyloid fibrils by monomer addition.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, accumulating evidence has indicated that soluble amyloid assemblies rather than the mature amyloid plaques may actually be the pathological culprits that result in the degenerative phenomena ( Figure 1) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%